2023
DOI: 10.3390/jcm12082944
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stroke Rehabilitation of Distal Upper Limb with New Perspective Technologies: Virtual Reality and Repetitive Transcranial Magnetic Stimulation—A Mini Review

Abstract: Upper extremity motor impairment is the most common sequelae in patients with stroke. Moreover, its continual nature limits the optimal functioning of patients in the activities of daily living. Because of the intrinsic limitations in the conventional form of rehabilitation, the rehabilitation applications have been expanded to technology-driven solutions, such as Virtual Reality and Repetitive Transcranial Magnetic Stimulation (rTMS). The motor relearning processes are influenced by variables, such as task sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…The gained information could be particularly useful for the diseases with motor symptoms. Several studies reported promising intervention effects for stroke and Alzheimer’s disease through non-invasive neurostimulation protocols ( Ahmed et al, 2023 , Banduni et al, 2023 , Kong et al, 2023 , Williams et al, 2009 ). These brain regions have in the future the potential to be targeted, after their relevance to upper extremity motor symptoms in patients have been assessed further.…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%
“…The gained information could be particularly useful for the diseases with motor symptoms. Several studies reported promising intervention effects for stroke and Alzheimer’s disease through non-invasive neurostimulation protocols ( Ahmed et al, 2023 , Banduni et al, 2023 , Kong et al, 2023 , Williams et al, 2009 ). These brain regions have in the future the potential to be targeted, after their relevance to upper extremity motor symptoms in patients have been assessed further.…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%
“…In fact, NIBS modulates the central nervous system by activating neurons in the brain and cortical excitability in order to further potentiate neuroplastic processes during rehabilitation training [ 49 ]. In particular, the combined use of VR and rTMS could improve the effects of rehabilitation by modulating the activity of damaged brain circuits to provide a beneficial effect [ 50 ]. This is why the integrated use of neuromodulation and the ecological virtual environment can lead to more benefits than the VR intervention alone.…”
Section: Innovative Technologies In Neurorehabilitationmentioning
confidence: 99%